THE ANALYSIS OF IMPLEMENTATION OF INDIA’S FOREIGN POLICY, “LOOK EAST POLICY” ON ASEAN INDIA STUDENTS EXCHANGE PROGRAMME PERIOD 2011-2016 - Melly Sabina Ester Lengkong (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2019)
This journal analyzes the implementation of India’s foreign policy ‘Look East Policy’ in ASEAN through ASEAN-India Students Exchange Programme (AISEP) in the period 2011-2016. AISEP program is a form of India’s Public Diplomacy in ASEAN. The objective of this research is to explore India’s goals from the AISEP concerning its foreign policy interests. All the explanations would be associated with the theory of diplomacy and the concept of Foreign policy, Regionalism, and Public Diplomacy. This research implies the qualitative methodology referring to data sources from library research, documentaries, and online. According to data shows that the AISEP program toward disseminating India’s modernity in the 21st century ever since its Look East Policy (1992) implemented. The progressive development of India’s economy has a positive effect on its foreign policy, which is a matter of interest to Southeast Asian countries, particularly ASEAN. Hence, this research describes the highly economic motivation referring to its dominated industrial visits. Another social and political visits to universities and government institutions were disseminating its growing economy also came from the high quality of its human resources and democracy.